Can Sustainable Livestock Systems and Alternative Proteins Address the Climate Crisis? Presentations - Ronchi, Loraine; Ringler, Claudia; Leroy, Jef L.; Stein, Stephanie von; Flintan, Fiona (2023)
Climate change is severely impacting our food systems, making it increasingly challenging to provide food security and healthy diets for all people. At the same time, food systems contribute 25–30% of all greenhouse gas emissions. The livestock sector alone contributes about half of these GHGs, and has a large land and water footprint.